The Roles of Envelope Glycoprotein M in the Life Cycle of Some Alphaherpesviruses - Li, Chunmei; Wang, Mingshu; Cheng, Anchun; Jia, Renyong; Yang, Qiao; Wu, Ying; Zhu, Dekang; Zhao, Xinxin; Chen, Shun; Liu, Mafeng; Zhang, Shaqiu; Ou, Xumin; et al. (Frontiers in Microbiology, 2021)
The envelope glycoprotein M (gM), a surface virion component that conserved among alphaherpesviruses, is predicted to be a multiple-transmembrane domain-containing glycoprotein with a complex N-linked oligosaccharide. The gM mediates a diverse range of functions during the viral life cycle. In this review, we summarize the biological features of gM, including its characterization and function. gM modulates the virus-induced membrane fusion during virus invasion, transports other proteins to the appropriate intracellular membranes for primary and secondary envelopment during virion assembly and promotes egress of virus. The gM can interact with various viral and cellular components, and the focus of recent research has also been on interactions related to gM. And we will discuss how gM participates in the life cycle of alphaherpesviruses.